The Forgotten Chamber: Right-Ventricular Functions in Juvenile Idiopathic Arthritis - ÖZBEN SADIÇ, BESTE (SPRINGER, 2012)
Cardiac involvement, such as pericarditis, myocarditis, and endocarditis, is seen in juvenile idiopathic arthritis. Although there have been some reports about right-ventricular systolic and diastolic functions of adults with rheumatoid arthritis and left-ventricular systolic and diastolic functions of children with JIA, there have been no studies about RV functions of children with JIA. The aim of this study was to determine RV functions in children with JIA. We performed conventional echocardiography and tissue Doppler imaging measurements of the right ventricle of patients with JIA. All patients were in sinus rhythm at the time of examination without overt LV heart failure and with normal LV ejection fraction. Fifty-five children with the diagnosis of JIA and 33 healthy control subjects were included in the study. Peak systolic, early, and late diastolic tricuspid annular velocities were significantly decreased in JIA patients compared with healthy controls (p < 0.05). Isovolumic accelaration (IVA), as a measure of myocardial acceleration during isovolumic contraction of the right ventricle, was also significantly lower in JIA patients than in healthy controls (p < 0.05). RV systolic and diastolic functions, in addition to the previously shown LV functions, are affected in JIA patients. IVA decreases in JIA patients and may be used as an alternative, noninvasive parameter for the assessment of RV systolic function in children with JIA.
Keywords: Juvenile idiopathic arthritis; Right ventricle; Echocardiography; RHEUMATOID-ARTHRITIS; CARDIAC INVOLVEMENT; CLASSIFICATION; DISEASE